The Effect of Brand Experience, Brand Awareness, and E-Word of Mouth on Customer Engagement of Cafe Customers in Yogyakarta - Sefulah; Audita Nuvriasari (LifeSciFi, 2025)
The rapid growth of cafés in Yogyakarta has intensified competition, making customer engagement crucial for sustaining loyalty and repeat purchases. In a digital environment, brand experience, brand awareness, and e-Word of Mouth (e-WOM) are key factors influencing how customers connect with cafe brands. This study aims to analyze the influence of brand experience, brand awareness, and e-WOM on customer engagement among cafe customers in Yogyakarta. The study uses a quantitative survey approach. The research sample consisted of 100 respondents who were users and buyers of cafe products or services in Yogyakarta, with the sampling technique using purposive sampling. The instrument tests confirmed that all data were valid and reliable, and the classical assumption tests indicated that the data were normally distributed with no multicollinearity or heteroscedasticity in the regression model. The results of the study showed that brand awareness and e-WOM partially had a positive and significant effect on customer engagement among cafe customers in Yogyakarta, while brand experience had no significant effect on customer engagement. These findings imply that cafés should prioritize strengthening brand visibility and encouraging positive online reviews to enhance engagement, as digital presence appears more influential than experiential factors alone.